2004
DOI: 10.4049/jimmunol.172.5.3215
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of IFN-γ-Producing (Th1-Like) Cells into the Inflamed Retina In Vivo Is Preferentially Regulated by P-Selectin Glycoprotein Ligand 1:P/E-Selectin Interactions

Abstract: Although there is evidence that altering the Th1/Th2 balance toward Th2 cells may be important in the resolution of Th1-type autoimmune disease, adoptive transfer of Th2 cells is not effective in protecting against Th1-type disease and may cause disease. Therefore, we examined the recruitment of Th1- and Th2-like cells into the retina in the murine autoimmune disease experimental autoimmune uveoretinitis. CD4 T cells were polarized in vitro to IFN-γ-producing Th1-like cells and non-IFN-γ-producing Th2-like cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 76 publications
3
61
0
Order By: Relevance
“…[46][47][48] However, even here it is selective because only certain subtypes of T cell, such as interferon gamma producing Th1 cells, readily cross the retinal vessels. 49 In addition, even when cells cross the vessels, they require to be activated systemically and to circulate for some time before they cross the vessels into the retina. 50 This applies to both T cells and monocytes and suggests that penetration of the barrier in inflammation requires the vessel wall to be 'made ready' for transendothelial migration, probably by weakening of the TJs.…”
Section: What Is Acaid and What Is Its Relationship To Immune Privilege?mentioning
confidence: 99%
“…[46][47][48] However, even here it is selective because only certain subtypes of T cell, such as interferon gamma producing Th1 cells, readily cross the retinal vessels. 49 In addition, even when cells cross the vessels, they require to be activated systemically and to circulate for some time before they cross the vessels into the retina. 50 This applies to both T cells and monocytes and suggests that penetration of the barrier in inflammation requires the vessel wall to be 'made ready' for transendothelial migration, probably by weakening of the TJs.…”
Section: What Is Acaid and What Is Its Relationship To Immune Privilege?mentioning
confidence: 99%
“…As indicated above, Th1 cells appear to be selectively recruited into the retina in this process. 20 These observations have clear significance for uveitis pathogenesis in humans. Assuming a similar process in autoimmune/immune-mediated IOI, extraocularly activated T cells likely circulate in the system for a variable period of time (weeks) before they breach the retinal barrier, implying that uveitis is a systemic disease initiated outside the eye.…”
Section: Pathology Of Non-infectious Ioi and Correlation With Experimmentioning
confidence: 97%
“…Furthermore, in E-selectin Ϫ/Ϫ mice treated with anti-P-selectin mAb, depletion of NK1.1 ϩ cells did not further augment the severity of lung fibrosis (Figure 7), suggesting that defective recruitment of NKT cells plays a major role in exacerbating lung fibrosis by the blockade of E-and P-selectins. Because it has been shown that P-and E-selectins preferentially mediate rolling and emigration of Th1 cells over Th2 cells, 36,37 E-and P-selectins may mediate the recruitment of NKT cells into the lung. In this study, CD3…”
Section: Discussionmentioning
confidence: 99%